Behavior of active mass damper (AMD) installed in high‐rise building during 2011 earthquake off Pacific coast of Tohoku and verification of regenerating system of AMD based on monitoring. Issue 4 (19th July 2013) - Yamamoto, Masashi; Sone, Takayuki
SUMMARY Active mass dampers (AMDs) have been installed in more than 50 buildings in Japan to control building vibrations. Most of these were used to improve the comfort of those inside the building during strong winds. The authors developed an AMD system with a regenerating system to save energy. The second application of this system was its installation in a 24‐story high‐rise building in Tokyo. Monitoring of the building and the AMD began in November 2010. Verifications of the system's vibration control performance and regenerating energy were conducted on the basis of the monitoring records. The 2011 earthquake off the Pacific coast of Tohoku shook this building and the AMD to a significant degree. The AMD was able to move under relatively strong vibrations by introducing a variable gain procedure. It also had a built‐in brake system and oil buffers to help manage excessive input. In the event of an earthquake, the brake system successfully worked as designed. After automatic restarting after braking, the variable gain control procedure effectively managed the stroke displacement within a controllable stroke limit. In addition to the control performance of the AMD, the energy consumption during typhoon no. 11 in 2011, the earthquake on September 15, 2011, and the Tohoku earthquake is presented. The results show that the regenerating system saved as much as 35–65% of the energy that would be consumed. Copyright © 2013 John Wiley & Sons, Ltd.